Age-Dependent Changes in Calcium Regulation after Myocardial Ischemia–Reperfusion Injury - Maria Bencurova; Terezia Lysikova; Katarina Leskova Majdova; Peter Kaplan; Peter Racay; Jan Lehotsky; Zuzana Tatarkova (Biomedicines, 2023)
During aging, heart structure and function gradually deteriorate, which subsequently increases susceptibility to ischemia–reperfusion (IR). Maintenance of Ca2+ homeostasis is critical for cardiac contractility. We used Langendorff’s model to monitor the susceptibility of aging (6-, 15-, and 24-month-old) hearts to IR, with a specific focus on Ca2+-handling proteins. IR, but not aging itself, triggered left ventricular changes when the maximum rate of pressure development decreased in 24-month-olds, and the maximum rate of relaxation was most affected in 6-month-old hearts. Aging caused a deprivation of Ca2+-ATPase (SERCA2a), Na+/Ca2+ exchanger, mitochondrial Ca2+ uniporter, and ryanodine receptor contents. IR-induced damage to ryanodine receptor stimulates Ca2+ leakage in 6-month-old hearts and elevated phospholamban (PLN)-to-SERCA2a ratio can slow down Ca2+ reuptake seen at 2–5 μM Ca2+. Total and monomeric PLN mirrored the response of overexpressed SERCA2a after IR in 24-month-old hearts, resulting in stable Ca2+-ATPase activity. Upregulated PLN accelerated inhibition of Ca2+-ATPase activity at low free Ca2+ in 15-month-old after IR, and reduced SERCA2a content subsequently impairs the Ca2+-sequestering capacity. In conclusion, our study suggests that aging is associated with a significant decrease in the abundance and function of Ca2+-handling proteins. However, the IR-induced damage was not increased during aging.